Trimethylacetic Anhydride-Based Derivatization Facilitates Quantification of Histone Marks at the MS1 Level - Kuchaříková, Hana; Dobrovolná, Pavlína; Lochmanová, Gabriela; Zdráhal, Zbyněk (Molecular & cellular proteomics, 2021)
Histone post-translational modifications (hPTMs) are epigenetic marks that strongly affect numerous processes, including cell cycling and protein interactions. They have been studied by both antibody- and MS-based methods for years, but the analyses are still challenging, mainly because of the diversity of histones and their modifications arising from high contents of reactive amine groups in their amino acid sequences. Here, we introduce use of trimethylacetic anhydride (TMA) as a new reagent for efficient histone derivatization, which is a requirement for bottom-up proteomic hPTM analysis. TMA can derivatize unmodified amine groups of lysine residues and amine groups generated at peptide N-termini by trypsin digestion. The derivatization is facilitated by microwave irradiation, which also reduces incubation times to minutes. We demonstrate that histone derivatization with TMA reliably provides high yields of fully derivatized peptides and thus is an effective alternative to conventional methods. TMA afforded more than 98% and 99% labeling efficiencies for histones H4 and H3, respectively, thereby enabling accurate quantification of peptide forms. Trimethylacetylation substantially improves chromatographic separation of peptide forms, which is essential for direct quantification based on signals extracted from MS1 data. For this purpose, software widely applied by the proteomics community can be used without additional computational development. Thorough comparison with widely applied propionylation highlights the advantages of TMA-based histone derivatization for monitoring hPTMs in biological samples.
Keywords: Chromatography, Liquid; Tandem Mass Spectrometry; histony; Acetylation; acetylace; bottom–up proteomics; Acetic Anhydrides; zvířata; myši; Protein Processing, Post-Translational; acetanhydridy; posttranslační úpravy proteinů; chemical derivatization; Mice; tandemová hmotnostní spektrometrie; chromatografie kapalinová; microwave irradiation; Histones; nádorové buněčné linie; histone post-translational modifications; Animals; Cell Line, Tumor; trimethylacetic anhydride